1976
DOI: 10.1159/000240835
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Values in Healthy Full-Term Nigerian Newborn Infants

Abstract: A study of haematological levels (haematocrits, reticulocyte and white cell counts) in healthy singleton full-term Nigerian neonates has shown significantly lower values than those of some previous reports but similar to others. The mean haematocrit of 60.8% on the 1st day dropped quite rapidly to 39.3% by the 4th week of birth. The mean reticulocyte count ranged from 3.8 to 1.9% on the 1st and 5th postnatal days, respectively. Adult level of less than 1 % was reached on the 6th day. Mean leucocyte count on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Prevalence of malarial infections at time of birth are presented in Table 3. The mean Hb levels obtained during the first 8 weeks of life were remarkably consistent with published reference values from normal Caucasian American, 22 Nigerian, 23 and Jamaican 24 populations ( Figure 2). However, in comparison with these reference populations, the standard deviations of mean Hb for the ABCP children were generally 0.8-1.3 g/ dL higher at each time point.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Prevalence of malarial infections at time of birth are presented in Table 3. The mean Hb levels obtained during the first 8 weeks of life were remarkably consistent with published reference values from normal Caucasian American, 22 Nigerian, 23 and Jamaican 24 populations ( Figure 2). However, in comparison with these reference populations, the standard deviations of mean Hb for the ABCP children were generally 0.8-1.3 g/ dL higher at each time point.…”
Section: Resultssupporting
confidence: 86%
“…As observed in many other populations throughout the world, male infants 6-24 months old had mean Hb values Ͻ0.5 g/ dL below the female means (P ϭ 0.010). 23 Differences by sex disappeared after 24 months. The mean Hb level was also associated with village of residence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effiong et al [9], in their study of Nigerian neo nates, found a mean WBC count of 12,400/mm3 and 15,860/mm3 on day 1 for males and females, respec tively. In the present study, we were unable to confirm any sex differences.…”
Section: Discussionmentioning
confidence: 94%
“…Normal hematological indices in the newborn have been established in the Caucasians and have been found not to be the same for African neonates. 4 5 6 Studies done by Onwukeme et al . in Jos, 4 Scot-Emuakpor et al .…”
Section: Introductionmentioning
confidence: 99%